Growth hormone releasing peptide-6 enhanced antibody titers against subunit antigens in mice (BALB/c), tilapia (Oreochromis niloticus) and African catfish (Clarias gariepinus). Issue 42 (9th October 2017) - Martínez, Rebeca; Hernández, Liz; Gil, Lázaro; Carpio, Yamila; Morales, Antonio; Herrera, Fidel; Rodríguez-Mallón, Alina; Leal, Yeny; Blanco, Aracelys; Estrada, Mario Pablo
Abstract: Modern subunit vaccines have excellent safety profiles and improved tolerability, but do not elicit strong immune responses without the addition of adjuvants. Developing a safe and affective adjuvant remains a challenge for peptide-based vaccine design. Growth Hormone Releasing Peptide-6 (GHRP-6) is one of the earliest-developed, synthetic, peptidyl growth hormone secretagogue receptor agonists. These compounds mimic the effect of the endogenous ligand, ghrelin. In the present study, we evaluated the ability of GHRP-6 to enhance the humoral immune response against co-injected antigens in mice, tilapia and African catfish. This peptide was able to increase the antigen-specific antibody response using heterologous proteins and peptides as antigens, which were also formulated in "water in oil" emulsions (Freund and Montanide). As long as we know there is no previous report describing any ghrelin analogous as molecular immunomodulator stimulating a humoral immune response. Further studies will be conducted to evaluate the functionality of this humoral immune response in challenge trials.